Memory trip. Fragments of the history of the railroad to the Pacific of Costa Rica - Agüero García, Javier (2020)
Received: 10-16-2019Approved: 11-29-2019 ABSTRACT  This essay addresses aspects of the Railroad to the Pacific within the historical perspective in order to assess its heritage significance, both in culture and in the institutional field. It begins with the description of the construction stage of this important means of transport, a process started in 1897; it is then passed to electrification, as the cornerstone of modernization; to finally move on to the approach of locomotives, true steel horses that made possible the transport of goods and passengers. It concludes with a reflection on the meaning of the state railway company, bastion of the economic, social and institutional development of the country, summarized in the attributes of speed, economy, security and efficiency.